Applications of Melatonin in Female Reproduction in the Context of Oxidative Stress. (29th July 2021) - Jiang, Yonghui; Shi, Huangcong; Liu, Yue; Zhao, Shigang; Zhao, Han
Abstract : Oxidative stress has been recognized as one of the causal mediators of female infertility by affecting the oocyte quality and early embryo development. Improving oxidative stress is essential for reproductive health. Melatonin, a self-secreted antioxidant, has a wide range of effects by improving mitochondrial function and reducing the damage of reactive oxygen species (ROS). This minireview illustrates the applications of melatonin in reproduction from four aspects: physiological ovarian aging, vitrification freezing, in vitro maturation (IVM), and oxidative stress homeostasis imbalance associated with polycystic ovary syndrome (PCOS), emphasising the role of melatonin in improving the quality of oocytes in assisted reproduction and other adverse conditions.